Recovering from nyaope addiction among young adults: A qualitative study in Tshwane, South Africa - Mathibe, Mmampedi; Mokwena, Kebogile (Al-Sihah: The Public Health Science Journal, 2025)
Substance abuse remains a major global health concern, with South Africa heavily impacted by nyaope use among young Black males in disadvantaged townships. Despite this, little is known about those who have successfully quit, revealing a gap in understanding recovery pathways. This qualitative phenomenological study used in-depth interviews to explore their experiences. A qualitative phenomenological study was conducted using in-depth interviews. The data were collected using the snowball method among a sample of 20 young people who managed to quit using nyaope in Tshwane, Gauteng province. NVivo was used for data analysis. The majority were single and unemployed with ages ranging from 26 to 40. About 15 (75%) in the age range 10 – 19 years started using nyaope in the adolescent phase. The number of participants who had been addicted to nyaope for over five years is 16 (80%). The longest period of being sober for two participants, 2 (10%) is over eight years. Themes identified were fast and easy journey to nyaope addiction, long periods of being addicted to nyaope, difficult journey to quitting nyaope addiction, and day-to-day dealing with post-addiction challenges of nyaope. Longer periods of addiction to nyaope were complicated by continuous relapse, which makes quitting nyaope not easy. Addiction to nyaope is complex due to its negative consequences. Therefore, recovery from nyaope addiction is a continuous, dynamic process requiring long-term support to prevent relapse. Participants highlighted the importance of a supportive environment. Recovery improves quality of life, reduces crime and violence, and strengthens social cohesion.